Circulating tumor cells in head and neck cancer: A review. Issue 2 (1st June 2016) - McMullen, Kyle P.; Chalmers, Jeffrey J.; Lang, Jas C.; Kumar, Pawan; Jatana, Kris R.
Abstract: Carcinoma of the head and neck represents 3.5% of all cancers, and the vast majority of these tumors are squamous cell carcinoma (HNSCC). With a stable overall survival rate of 50% among all stages, there is continued interested in developing measures for early detection and disease aggressiveness. Circulating tumor cells (CTCs) have been identified as a potential marker for early metastatic disease, response to treatment, and surveillance in head and neck squamous cell carcinoma. In this article, techniques of CTC detection, applications of CTC technology, and outcomes of HNSCC patients will be discussed.